Overexpression of LINC00672 promotes autophagy in Alzheimer's disease by upregulating GPNMB. - Lingyi Gao; Shijun Hu; Yan Lv; Guoxian Zheng; Zhichuan Lin (PLoS ONE)
Background Alzheimer's disease (AD) is an irreversible neurodegenerative brain disorder, and autophagy crafts a new dawn on AD therapeutics. However, whether LINC00672 exerts its biological effects involvement in autophagy-mediated mechanisms in AD remain obscure. Methods SH-SY5Y cells were treated with Amyloid Beta 1-42 (Aβ1-42, Aβ), while an AD mouse model was established using streptozotocin (STZ). The effects of LINC00672 overexpression on cell proliferation, apoptosis, and autophagy were evaluated in Aβ-stimulated SH-SY5Y cells. Besides, the impact of LINC00672 on cognitive function and pathological changes of the hippocampal tissues were validated in AD mice. Additionally, the interaction between LINC00672 overexpression and GPNMB silencing were determined in vitro. Results Aβ stimulation diminished viability, augmented apoptosis, restricted the activation of autophagy in SH-SY5Y cells, while these alterations were partially abolished by LINC00672 overexpression. Furthermore, LINC00672 upregulation could improve cognitive impairment, and attenuate neuronal damage and even death in the STZ-treated AD mice. Additionally, GPNMB knockdown aggravated the improved neuronal injury and relatively restrained autophagy in Aβ-stimulated cells after LINC00672 overexpression. Conclusions LINC00672 exerted a protective effect in the AD progression by upregulating GPNMB to promote autophagy.